2004
DOI: 10.1002/bit.10829
|View full text |Cite
|
Sign up to set email alerts
|

In vitro laser ablation of laboratory developed biofilms using an Nd:YAG laser of 532 nm wavelength

Abstract: We studied the laser ablation of laboratory-developed biofilm on titanium and glass surfaces. Specifically, Pseudoalteromonas carrageenovora, a marine biofilm forming bacterium was used to generate laboratory biofilm. Two fluences, 0.05 and 0.1 J/cm(2) and three durations of irradiation, 30 s, 5 min, and 10 min were tested using an Nd;YAG laser of 532 nm wavelength (in the green light area). Nonirradiated coupons with biofilm served as control. The biofilm removal efficiency increased with the increase in lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…It has also proven useful for quantitative biofilm analysis, especially to confirm findings obtained by quantitative (viable count, CV staining) or other imaging (light microscopy, SEM) techniques (Ansari et al, 2013;Chatterjee et al, 2014;Li et al, 2015;Salunke et al, 2014). Among the characteristics of the sample surface examined, height and roughness analyses from AFM images allow quantification of biofilm biomass in terms of thickness and EPS amount, respectively (Ansari et al, 2013;Chatterjee et al, 2014;Danin et al, 2015;Li et al, 2015;Mangalappalli-Illathu et al, 2008;Nandakumar et al, 2004;Qin et al, 2009;Sharma et al, 2010).…”
Section: ;mentioning
confidence: 99%
“…It has also proven useful for quantitative biofilm analysis, especially to confirm findings obtained by quantitative (viable count, CV staining) or other imaging (light microscopy, SEM) techniques (Ansari et al, 2013;Chatterjee et al, 2014;Li et al, 2015;Salunke et al, 2014). Among the characteristics of the sample surface examined, height and roughness analyses from AFM images allow quantification of biofilm biomass in terms of thickness and EPS amount, respectively (Ansari et al, 2013;Chatterjee et al, 2014;Danin et al, 2015;Li et al, 2015;Mangalappalli-Illathu et al, 2008;Nandakumar et al, 2004;Qin et al, 2009;Sharma et al, 2010).…”
Section: ;mentioning
confidence: 99%
“…Our earlier studies showed that low-power laser irradiation from an Nd:YAG laser resulted in a substantial bacterial, microalgal, and invertebrate larval mortality (Nandakumar et al, 2002a -c). In addition, observations carried out on biofilms also showed that laser irradiation could significantly remove biofilms formed on hard surfaces within a very short period of time (Nandakumar et al, 2003b). According to our earlier studies, laser irradiation from a pulsed laser with fluence 0.1 J/cm 2 removed more than 90% of natural biofilm formed on coupon surfaces.…”
Section: Introductionmentioning
confidence: 56%
“…They were used as received. Coupon preparation was carried out as explained in Nandakumar et al (2003b).…”
Section: Experimental Couponsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many techniques have been developed to control or remove biofilms -electrical fields (Blenkinsopp, Khoury, & Costerton, 1992), laser irradiation (Nandakumar, Obika, Utsumi, Ooie, & Yano, 2004), vibration (Bott, 2000), micro-jets (Bayoudh, Ponsonnet, Ben Ouada, Bakhrouf, & Othmane, 2005), chlorine (Chen & Stewart, 2000) and the like -but all of these techniques have disadvantages. Chlorine is an excellent biocide and relatively cheap, but its oxidation products are generally toxic and may even be carcinogenic (Bott, 2000).…”
Section: Introductionmentioning
confidence: 99%